Binary Population Synthesis: Low- and Intermediate-Mass X-Ray Binaries - Podsiadlowski, P; Rappaport, S; Pfahl, E (2001)
As has only recently been recognized, X-ray binaries with intermediate-mass secondaries are much more important than previously believed. To assess the relative importance of low- and intermediate-mass X-ray binaries (LMXBs and IMXBs), we have initiated a systematic study of these systems consisting of two parts: an exploration of the evolution of LMXBs and IMXBs for a wide range of initial masses and orbital periods using detailed binary stellar evolution calculations, and an integration of these results into a Monte-Carlo binary population synthesis code. Here we present some of the main results of our binary calculations and some preliminary results of the population synthesis study for a ``standard'' reference model. While the inclusion of IMXBs improves the agreement with the observed properties of ``LMXBs'', several significant discrepancies remain, which suggests that additional physical processes need to be included in the model.